Do parental attitudes toward and expectations for their children's education and future jobs matter for their children's school achievement?. (11th September 2017) - Tan, Cheng Yong
Abstract : The traditional discourse in the scholarship on cultural capital theory has focused on how exclusive participation in elite status culture by students from higher socioeconomic status families benefits their learning in schools, the effects of which are most evident in linguistic subject areas such as reading achievement. However, some scholars have argued that cultural capital is not restricted to elite status culture but could include parental familiarity with school evaluation standards and job market requirements, and that the effects could transcend languages to include performance domains with more objective evaluation that are susceptible to school influences (e.g. mathematics and science). The present study systematically examines this position using data involving 96, 591 15‐year‐old students from 3602 schools in eight countries who participated in the Programme for International Student Assessment 2012. Results of three‐level hierarchical linear modelling showed positive relationships between seven cultural capital variables and student mathematics achievement. The cultural variables comprised: home educational resources; parental educational attainment and occupational status; parental expectations of their children's educational attainment, future career in mathematics and school; and parental valuing of mathematics. In particular, the three parental expectations variables had substantively larger effect sizes on student achievement than the other cultural capital variables. The results demonstrated that parental familiarity with school evaluation standards and future job requirements, especially as measured by parental expectations, may constitute cultural capital that privileges student mathematics achievement in schools.